If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -6 = 5y + 6 Reorder the terms: -6 + 2y = 5y + 6 Reorder the terms: -6 + 2y = 6 + 5y Solving -6 + 2y = 6 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -6 + 2y + -5y = 6 + 5y + -5y Combine like terms: 2y + -5y = -3y -6 + -3y = 6 + 5y + -5y Combine like terms: 5y + -5y = 0 -6 + -3y = 6 + 0 -6 + -3y = 6 Add '6' to each side of the equation. -6 + 6 + -3y = 6 + 6 Combine like terms: -6 + 6 = 0 0 + -3y = 6 + 6 -3y = 6 + 6 Combine like terms: 6 + 6 = 12 -3y = 12 Divide each side by '-3'. y = -4 Simplifying y = -4
| (X-3)x=550 | | 7-3x=7-4x+x | | 2x-2=18x+6 | | 30+34-x=13x-5x+37 | | 2z+5=4x-9 | | 1-(-4-n)=3(n+3) | | 5x^2+20xy-40y= | | 9-(-9)+(-4)= | | x+2x+6x+3=21 | | 4y^3-5y^2-12y+15= | | Y(7+3)=5 | | (-7)+2+(-5)= | | -2(1-3x)-x=-2-6x | | 4y^3-5y^2-12y-15= | | 5(a-12)+(2a+15)=a-9 | | 8x-7x=-(1-2x)-7(x+5) | | 5/3x-5=3x+7 | | (-8)-7-(-2)= | | 3x=82+1x | | 2p-9p=49 | | 9n^2-9= | | 7(7-2x)-6=-5(-8+4x)-3 | | y=58-4z | | 5x^4-7x^2=-2 | | 4=6x-2(2x-7) | | 1184=16t^2 | | (-1)-(-2)-9= | | -8=6z | | 12q-a=b+7+4q | | 2(x+1.3)-4(5-x)=15 | | 2(x+1.3)4(5-x)=15 | | 7(a+1)-3a=5+4(2s-1) |